2015
DOI: 10.1007/s11832-015-0705-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional improvement after hip arthroscopy in cases of active paediatric hip joint tuberculosis: A retrospective comparative study vis-à-vis conservative management

Abstract: PurposeTuberculosis of the hip joint is a significant cause of preventable disability, especially in children. The aim of our study was to evaluate the functional results of hip arthroscopy done in a cohort of patients with hip joint tuberculosis and to compare them with the outcome of conservatively managed cases.MethodsThis was a retrospective cohort study in which we evaluated the records of 22 hip arthroscopies performed in known cases of tuberculosis of the hip joint in children less than 12 years of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, there have been few reports on the treatment of shoulder tuberculosis by arthroscopy. In other joint tuberculosis, the treatment with arthroscopy has achieved good results [19][20][21]. This is similar to the clinical results achieved in this study.…”
Section: Discussionsupporting
confidence: 88%
“…However, there have been few reports on the treatment of shoulder tuberculosis by arthroscopy. In other joint tuberculosis, the treatment with arthroscopy has achieved good results [19][20][21]. This is similar to the clinical results achieved in this study.…”
Section: Discussionsupporting
confidence: 88%
“… 7 , 22 , 23 Moon et al 24 reported open surgical debridement or synovectomy combined with postoperation immobilization to treat pediatric HTB, with a good result of 73.1%. Tiwari et al 25 described hip arthroscopy as an effective and safe minimally invasive procedure in the treatment of pediatric HTB, which seemed to have more advantages in earlier return to activity, less invasive and less perioperative morbidity when compared with the open procedure. They also described the involvement of the labrum under arthroscopy might indicate a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The other difference between open surgery and arthroscopy procedure was the use of postoperative spica. After open surgical debridement, some authors recommended a hip spica for 4 to 6 weeks or even several months, which usually was absent for the arthroscopy procedure 24–26…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few reports on the treatment of shoulder tuberculosis by arthroscopy. In other joint tuberculosis, the treatment with arthroscopy has achieved good results [16][17][18] . This is similar to the clinical results achieved in this study.…”
Section: Arthroscopy For the Treatment Of Shoulder Tuberculosismentioning
confidence: 99%